Molecular analyses reveal high species diversity of trematodes in a sub-Arctic lake - Soldánová, Miroslava; Georgieva, Simona; Roháčová, Jana; Knudsen, Rune; Kuhn, Jesper A; Henriksen, Eirik H; Siwertsson, Anna; Shaw, Jenny C; Kuris, Armand M; Amundsen, Per-Arne; Scholz, Tomáš; Lafferty, Kevin D; et al. (International Journal for Parasitology, 2017)
To identify trematode diversity and life-cycles in the sub-Arctic Lake Takvatn, Norway, we characterised 120 trematode isolates from mollusc first intermediate hosts, metacercariae from second intermediate host fishes and invertebrates, and adults from fish and invertebrate definitive hosts, using molecular techniques. Phylogenies based on nuclear and/or mtDNA revealed high species richness (24 species or species-level genetic lineages) and uncovered trematode diversity (16 putative new species) from five families typical in lake ecosystems (Allocreadiidae, Diplostomidae, Plagiorchiidae, Schistosomatidae and Strigeidae). Sampling potential invertebrate hosts allowed matching of sequence data for different stages, thus achieving molecular elucidation of trematode life-cycles and exploration of host-parasite interactions. Phylogenetic analyses also helped identify three major mollusc intermediate hosts (Radix balthica, Pisidium casertanum and Sphaerium sp.) in the lake. Our findings increase the known trematode diversity at the sub-Arctic Lake Takvatn, showing that digenean diversity is high in this otherwise depauperate sub-Arctic freshwater ecosystem and indicating that sub-Arctic and Arctic ecosystems may be characterised by unique trematode assemblages.
Keywords: hlemýždi; Phylogeny; Snails; Trematoda; Fish Diseases; měkkýši; zvířata; genetická variace; Arktida; Lakes; ryby; infekce červy třídy Trematoda; Fishes; hmyz; jezera; Norsko; Bayesova věta; ekosystém; Sequence Alignment; Norway; bezobratlí; Ecosystem; Invertebrates; nemoci ryb; sekvenční seřazení; Arctic Regions; Genetic Variation; Bayes Theorem; Animals; Mollusca; mlži; fylogeneze; Bivalvia; Insecta; Haplotypes; haplotypy; Amphipoda; Trematode Infections